Elucidating feline hepatic lipidosis through serum biochemistry, histopathology and gene expression in the Klang valley stray cats - Salleh, Muhammad Fadzly (2020)
Feline hepatic lipidosis (FHL) is a common metabolic dysfunction related to lipid metabolism in cats. In conditions of hepatic lipidosis, steatosis or excessive lipid deposition occurs in the liver due to the cat’s inability to efficiently breakdown and utilise the excess lipids. As such, lipid vacuolation in the hepatocytes and associated clinical signs, may arise if the condition worsens. The main cause of hepatic lipidosis remains unclear. This study aims to determine the lipid composition of liver samples in Klang Valley stray cats and to relate their serum and liver biochemistry with their histopathological changes, alongside identifying expression of hepatic genes associated with energy regulation through lipid metabolism associated with FHL in stray cats. In total, 18 stray cats that were emaciated, dehydrated and lethargic were collected from pounds located in the Klang Valley area. Alanine aminotransferase (ALT), a common biomarker to determine liver injury in small animals, was measured in cat blood serum, as well as creatinine and urea in determining kidney function. Triglycerides (TAG) and cholesterol concentrations were measured in serum through serum analysis and in liver samples through Bligh & Dyer lipid extraction to relate to their steatosis levels. Histological analysis of liver samples were carried out to determine the severity of fatty change of the liver (FCL). Through this study, cats with increasing severity of FCL in liver histology was observed to have increased levels of serum ALT, creatinine and urea, signifying liver injury, renal challenges and dehydration. However, TAG levels in serum seemed to decrease with increasing severity of lipid vacuolation, with an increase of TAG concentration in liver sections extracted for total lipids. Peripheral fats break down into free fatty acids and enter the liver through the blood stream, hence, the lower levels of serum TAG despite increasing severity of liver steatosis. Serum and liver cholesterol levels exhibit the same trend in TAG movement: decreasing serum cholesterol levels against increasing severity of FCL in contrast to increased liver cholesterol concentrations with FCL severity. Expression of PPAR-γ was observed, indicating macrophage activity which may be involved in hepatic recovery as well as fatty acid oxidation. PPAR-δ expression was observed as well, a signifier of increased lipogenesis and consequently induction of inflammatory reactions. Blood biomarkers (ALT, TAG, urea and creatinine) and liver TAG concentrations reflect on the histopathological changes in FHL cats in correlation to their FCL severity, coupled with hepatic gene expression of PPAR-δ and PPAR-γ in promoting hepatic recovery from FHL. These blood biomarkers in addition to further studies into blood-gene expression of the PPAR constituents could lead to earlier and less invasive diagnosis of FHL in cats.